Myeloablative haploidentical hematopoietic stem cell transplantation using basiliximab for graft-versus-host disease prophylaxis. Issue 6 (July 2015) - Huang, Rui; Tu, Sanfang; Deng, Lan; Kang, Qian; Song, Chaoyang; Li, Yuhua
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives We retrospectively compared the prophylactic effect of basiliximab and antithymocyte globulin (ATG) after haploidentical hematopoietic stem cell transplantation (HSCT) in patients with leukemia. Methods Haploidentical HSCT using basiliximab for graft-versus-host disease (GVHD) prophylaxis in 10 patients with leukemia was retrospectively compared to ATG for GVHD prophylaxis in 24 patients. Results All the patients achieved neutrophil engraftment. One patient in the ATG group did not achieve platelet engraftment. The incidence of grade II–IV and grade III–IV acute GVHD was 30 and 20%, respectively, in the basiliximab group and 16.7 and 4.2%, respectively, in the ATG group (P > 0.05). Extensive cGVHD developed in 40 and 22.2% of patients in the basiliximab group and ATG group, respectively (P > 0.05). Basiliximab resulted in mild infection and a low incidence (10%) of infection-related mortality; ATG resulted in relative severe infection with 29.2% infection-related mortality (P > 0.05). During the follow-up period, 20% of the basiliximab group and 22.7% of the ATG group relapsed (P > 0.05). In the basiliximab group and the ATG group, the 3-year accumulative overall survival rate was, respectively, 80 and 52.5% and the 3-year leukemia-free survival, respectively, was 60 and 49.6% (P > 0.05). Discussion The incidences of grade II–IV and grade III–IV aGVHD in the basiliximab group were similar to those in halpoidentical HSCT containing ATG. Compared to the ATG group, the basiliximab group had a lower rate of transplantation-related mortality and better long-term survival, but without statistical significance. Conclusion The prophylactic regimen of basiliximab with haploidentical HSCT against GVHD seems safe and promising. More studies needed to verify this.